2021
DOI: 10.1097/scs.0000000000007398
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Care of Cleft Lip and Palate: Analysis of Dentofacial Orthopedic and Orthognathic Treatments

Abstract: Group B: Patients <10 years old, with alveolar cleft and oronasal communication, without previous attempt to close it. Group C: Patients <10 years old, with alveolar cleft and oronasal communication, and having already had at least 1 attempt to close it. Group D: Patients 10 to 18 years old, without alveolar cleft (already closed). Group E: Patients 10 to 18 years old, with alveolar cleft and oronasal communication, without previous attempt to close it. Group F: Patients 10 to 18 years old, with alveolar cleft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The maxillary arch tends to show a post-therapeutic reduction of its transversal and sagittal dimensions [ 6 , 15 ]. Palatal scar tissue probably compromises stability in patients with CLP [ 16 ]. In patients with unilateral CLP, Sumardi et al identified the following factors for a long-term relapse: age at the end of treatment, gap closure in agenesis of the lateral incisor and occlusion at the end of treatment [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The maxillary arch tends to show a post-therapeutic reduction of its transversal and sagittal dimensions [ 6 , 15 ]. Palatal scar tissue probably compromises stability in patients with CLP [ 16 ]. In patients with unilateral CLP, Sumardi et al identified the following factors for a long-term relapse: age at the end of treatment, gap closure in agenesis of the lateral incisor and occlusion at the end of treatment [ 17 ].…”
Section: Introductionmentioning
confidence: 99%